Relation Analysis in Rural Space – A Research Method for Exploring the Spatial Structure in Hungary – - Szörényiné Kukorelli, Irén (Discussion Papers, 2012)
This paper is introducing a method for analysing the differences and dynamics of the social utilisation of space. The essence of this method lies in the registration of changes in the spatial structure of settlements through analysing the spatial shifts of settlements within settlement network hierarchy with the identification of coherent spatial units. The analysis of spatial relations, i.e. microregional planning is a very useful method as it helps in mapping the interrelationship of settlements, and their major linking points, as well as in identifying their positions in the settlement hierarchy and - through the analysis of the directions of gravitational force - may localise their gravitational zones as well. Hereinafter, this method will be named as spatial relationship analysis. The startup phase for the workout of this method was funded by the Hungarian Scientific Research Fund's Programme titled `The Integration Ability of Rural Spaces in Hungary's Socio-economic Process'.